DISIPLIN BELAJAR WARGA BELAJAR DI PKBM KAK SETO KOTA PEKANBARU - Ruth Novianti; Said Suhil Achmad; Jasfar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the Learning Discipline of Learning Citizens. The formulation of the problem in this study is How high is the discipline of learning citizens learning in PKBM Kak Seto Pekanbaru City ?. Are there variations in the learning disciplines of citizens studying at PKBM Kak Seto Pekanbaru City based on gender, age, package (ABC), and marital status ?. And the purpose of this study is the level of learning discipline of learning citizens in PKBM Kak Seto Pekanbaru City, differences in the learning discipline of citizens learning in PKBM Kak Seto Pekanbaru City based on gender, age, package (ABC), and marital status. This study has 4 indicators, namely (1) mental attitude to obey the rules of learning, (2) obey the rules in the classroom, (3) self-control in learning, (4) adjustment in learning in class. The population in this study was 66 people learning. The sample in this study used a proportional stratified random sampling technique. The sample in this study was taken from all residents learning package A, B and C at PKBM Kak Seto Pekanbaru City as many as 40 people and 20 people for the trial. The data collection technique in this study was a questionnaire technique. Of the 52 statement items tested, found 2 invalid and 50 valid statements. Researchers discard invalid statements, because they do not interfere with other statements. Based on the results of the study an average of 4 indicators of the mean value for the Learning Residents variable. The formulation of the problem in this study was: How high is the discipline of learning citizens learning in PKBM Kak Seto, Pekanbaru City is classified as high, namely with a mean of 3.83 and an elementary school of 0.8. And the best of the 4 indicators is the mental attitude to obey the rules of learning with a mean of 3.93 and SD 0.75.Key Words: Discipline, Learning Discipline Citizens Learning